INHIBITORY ACTIVITY OF ARTEMISIA ANNUA L. EXTRACTS AGAINST SARS-COV-2 CORONAVIRUS - Zhurinov , M.; Miftakhova , A.; Shustov , A.; Keyer , V.; Solodova , E. (Eurasian Journal of Applied Biotechnology, 2022)
The article describes preparing extracts of Artemisia annua L. and the use of the extracts to compare the virus-inhibiting activity against the coronavirus SARS-CoV-2. The extracts were prepared using hot water, water-alcohol mixture and butanol. The extracts were tested in screening-format tests on Vero E6 cells to measure the cytotoxicity and antiviral activity. Values of 50% inhibitory concentration (IC50) which measure the cytotoxicity were as follows: for the hot-water extract - 1587 µg/ml, for butanol extract - 713 µg/ml, and for water-alcohol extract >2000 µg/ml. The quite high IC50 values indicate that the hot-water and butanol extracts have little cytotoxicity, and the water-alcohol extract is not toxic in vitro. Protection from the virus-induced cytopathic effect was observed in infected cultures upon addition of the extracts. Concentrations at which the extracts demonstrate the highest protection were measured by counting densities of live cells (in infected cultures)using the MTT-test. The results of the MTT-testin a form of dependence of optical densities from extracts’ concentrations are presented in the paper. All three extracts show the ability to inhibit the replication of the SARS-CoV-2 virus. For hot-water and butanol extracts, the peak density of live cells in infected cultures was observed when the extracts were present at the concentration of 667 μg/ml;however at the higher concentration (2000 µg/ml), both extracts inhibit cell growth. However, none of the three extracts at the optimal concentration completely suppress viral replication.The work needs to be continued to produce an effective herbal drug against the SARS-CoV-2 virus.